Field efficacy of some newer chemical insecticides against stem borer, Nupserha sp. near vexator (Pascoe) in sunflower (Helianthus annuus L.): FIELD EFFICACY OF NEWER CHEMICAL INSECTICIDES AGAINST STEM BORER IN SUNFLOWER - N E JAYEWAR; B V PATIL; H BASAPPA (Journal of Oilseeds Research, 2015)
A field experiment was conducted to evaluate the efficacy of some newer chemical insecticides viz., thiodicarb 75WSP, indoxacarb 14.5SC, spinosad 45SC, profenophos 50EC, dichlorovos 76EC and chlorpyrifos 20EC against stem borer Nupserha sp. near vexator in sunflower at Oilseeds Research Station, Latur, Maharashtra. Results revealed that all the treatments were significantly superior in reducing the population of stem borer over untreated control. Among the insecticides, indoxacarb @ 1ml/l was most effective and was found on par with spinosad @ 0.3ml/l, profenophos @ 2ml/l and thiodicarb @ 2gm/l. Highest seed yield was recorded with spinosad (1416 kg/ha) and found on par with indoxacarb (1401 kg/ha) whereas the lowest yield was observed in untreated control (1010 kg/ha). The maximum incremental benefit cost ratio was obtained with application of chlorpyrifos (4.96) followed by indoxacarb (4.27), profenofos (3.43), and spinosad (3.09).